Electrical behavior of silver particulate films deposited on 8 MeV electron beam irradiated softened polystyrene substrates - Pattabi, Manjunatha; Gurumurthy, S. C.; Sanjeev, Ganesh; Gaikwad, A. B. (Journal of Materials Science-Materials in Electronics, 2011)
Results of the investigations carried out on the electrical behavior of silver particulate films deposited on electron beam irradiated polystyrene (PS) coated substrates held at a temperature of 455 K in a vacuum of 8 x 10(-6) torr at a constant deposition rate of 0.4 nm/s are reported. It is known that when metals are evaporated on to softened polymer substrates, subsurface particulate structures are formed whose morphology is dependent on deposition parameters. Further, it was shown that the morphology is dependent on polymer-metal interaction. The present work demonstrates that the polymer-metal interaction can be brought about in inert polymers like PS by electron irradiation. The results indicate that the films deposited on PS irradiated to a dose of 20 and 25 kGy gives rise to smaller clusters with smaller inter-cluster separation, better suited for sensor applications. The induced polymer-metal interaction is attributed to the creation of free radicals due to the 8 MeV electron irradiation.

Morphological changes in nanoparticulate silver films due to electron beam irradiation of polystyrene substrates - Pattabi, Manjunatha; Gurumurthy, S. C.; Sanjeev, Ganesh; Gaikwad, A. B. (Nuclear Instruments & Methods in Physics Research Section B-Beam Interactions With Materials and Atoms, 2011)
Results of the studies on the effect of 8 MeV electron beam irradiation of polystyrene substrates on the morphology of silver particulate films deposited at 455 K in a vacuum of 8 x 10(-6) Torr are reported. Optical absorption studies show the presence of transverse and longitudinal plasmon resonance for films deposited on irradiated polystyrene. Scanning electron microscopy reveals a decrease in particle size with smaller inter-particle separation for irradiated films. Larger clusters are formed in the case of films deposited on polystyrene after 300 h of irradiation. In this paper, we show that the morphology of silver nanoparticulate films can be modified by electron irradiation of inert polymer substrates like polystyrene. The change observed due to irradiation is attributed to the formation of free radicals, thereby altering the polymer-metal interaction. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Electron bombardment; Optical properties; Particulate films; Polymers; Silver; surface morphology